Facile Synthesis of Porous Coralline LiVO3 as High‐Performance Li‐Ion Battery Cathodes. Issue 2 (9th January 2018) - Zhao, Dong; Dong, Chongrui; Pu, Xiangjun; Huang, He; Fu, Xifan; Chen, Zhongxue
Abstract: A facile and easily scaled‐up polymer‐pyrolysis method is developed to synthesize porous coralline LiVO3 as cathodes for lithium‐ion batteries (LIBs). Polyacrylates of Li and V are used as the precursor compounds. The nanostructured LiVO3 delivers a high specific capacity of 307.6 mAh g −1 with a remarkable capacity retention of 80.6% after 100 cycles. In addition, a high energy density close to 800 Wh kg −1 as well as a competitive power density of ∼4500 W kg −1 are attained. Such excellent lithium storage performance derives from its porous nanoarchitecture, which not only supplies numerous active sites for electrochemical reactions, and shortens Li‐ions diffusion distance, but also provides enough void space to buffer the volume change during lithium intercalation and deintercalation. Therefore, the porous coralline LiVO3 justifies its potential practical application as an alternative to high energy and high power electrode materials for lithium‐ion batteries. The simple approach opens up a new way to fabricate other types of porous coralline energy storage materials. Abstract : High performance LiVO3 : Porous coralline LiVO3 is prepared by a facile polymer‐pyrolysis method. The resultant cathodes exhibit superior cycle stability and rate capability in lithium‐ion batteries